Pengaruh Pelatihan Terhadap Kinerja Karyawan Di PT. Bank Perkreditan Rakyat Solok Sakato - Zuraedah Indah; Iljasmadi Iljasmadi (JURNAL PUNDI, 2020)
Problems that exist in PT Bank Perkreditan Rakyat Solok Sakato is lack of motivation, as well as the lack of employee working ability is suspected to be the cause of low employee performance. This study aims to determine the effect of Training on Employee Performance at PT. Bank Perkreditan Rakyat (BPR) Solok Sakato. Population in this research is all employees of PT. Bank Perkreditan Rakyat (BPR) Solok Sakato. This research was conducted on September to October 2017 which amounted to 18 respondents, all employees are used as sample research, sampling technique using total sampling technique means that the whole population is sampled. The research instrument used questionnaire with Likert Scale model, while the data analysis technique is simple regression. The effect of correlation (R) is 0.463, that is, there is moderate and positive relationship between training to performance and determination coefficient value or R square (R2) 0,215 meaning tha0t training contribution to performance is 0,215 or 21,5% and equal to 78,5%. Impact of training on performance with regression equation Y = 46,591 + 0,407 x It means that every increase of value Training one unit then performance will increase 0,407 unit and vice versa if training value minus one unit then performance will decrease 0,407. Whereas if the value of training is assumed to be zero or absent, then the performance remains at 46,591 units. Training that has been given to employees at PT. Bank Perkreditan Rakyat Solok Sakato, in order to complete the work in each part. Employee performance at PT. People's Credit Bank Solok Sakato, which has been well maintained or further enhanced